2008
DOI: 10.1371/journal.pone.0003297
|View full text |Cite
|
Sign up to set email alerts
|

Arp2/3 Branched Actin Network Mediates Filopodia-Like Bundles Formation In Vitro

Abstract: During cellular migration, regulated actin assembly takes place at the cell leading edge, with continuous disassembly deeper in the cell interior. Actin polymerization at the plasma membrane results in the extension of cellular protrusions in the form of lamellipodia and filopodia. To understand how cells regulate the transformation of lamellipodia into filopodia, and to determine the major factors that control their transition, we studied actin self-assembly in the presence of Arp2/3 complex, WASp-VCA and fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 34 publications
5
66
0
Order By: Relevance
“…Now the filaments can bend toward each other, enabling fascin to crosslink them into finger-like bundles, resulting in a structural transition from a dense aster to a large star-like structure. [28,29] The similarity between the aster-to-star and the lamellipodium-tofilopodia transitions underlies our in vitro experimental studies and their theoretical interpretations.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Now the filaments can bend toward each other, enabling fascin to crosslink them into finger-like bundles, resulting in a structural transition from a dense aster to a large star-like structure. [28,29] The similarity between the aster-to-star and the lamellipodium-tofilopodia transitions underlies our in vitro experimental studies and their theoretical interpretations.…”
Section: Introductionmentioning
confidence: 56%
“…alyze theoretically a series of in vitro experiments, partly described here and in more detail elsewhere, [28,29] which appear to support the first mechanism. More explicitly, in the next section we show, both experimentally and theoretically, that in the presence of fascin, a dense and highly branched aster-like network of actin filaments exhibit a transition to a star-like structure, where bundles of filaments emanate and grow radially from the aster-like core.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…This idea is consisted with results obtained in reconstitution studies that showed that more and longer actin bundles were formed in vitro, when the concentration of the Arp2/3 complex was decreased, while the concentrations of other components, such as WASP-VCA, actin and fascin, kept constant. 87 A naturally high rate of lamellipodia-tofilopodia transition is observed in neuronal growth cones, which do not form extensive lamellipodia, but rapidly reorganize their small lamellipodial regions into filopodia. 27 Another factor that may contribute to this phenomenon in Arp2/3 complex knockdown cells is that when actin monomers are less consumed by Arp2/3 complex, a higher concentration of them becomes available for actin filament elongation, thus shifting the actin dynamics at the leading edge toward filopodia.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…3 Networks and clusters of actin bundles are observed at high concentrations of different cross-linkers such as espin, fascin, aactinin, and filamin. 4 Self-organized asters emerge in actin-myosin-fascin 5 and actin-Arp2/3 complex-fascin 6 systems. Microtubule-motor systems also self-organize into asters, vortices, and networks 7 and the self-organization is influenced by the size of the confinement.…”
Section: Introductionmentioning
confidence: 99%